Antibacterial Activity of Lyophilized Aqueous Extract of Coriaria Myrtifolia from Northern Morocco - Hezbri, Karima; Hafse, Maha; Farah, Abdellah; Sbissi, Imed; Gtari, Maher; Fikri Benbrahim, Kawtar (JOURNAL OF ADVANCES IN BIOTECHNOLOGY, 2014)
This work aims to evaluate the antibacterial activity of lyophilized aqueous extract of Coriaria myrtifolia against twenty three bacterial strains belonging to twelve main genera, known to be involved in some pathologies and /or in the food spoilage process: Bacillus sp., E. coli, E. hafnia, Enterococcus sp., Klebsiella sp,. Listeria monocytogenes, Pseudomonas sp., Salmonella sp., Serratia sp., Shigella sp., S. aureus and Streptomyces sp. To achieve this goal, the disk diffusion method was used. The study revealed that C. myrtifolias aqueous extract is active against most of the tested strains and that activity is proportional to its concentration. The intensity of inhibition depends on the extracts concentration on one hand and on thebacterial species tested on the other hand.